Antibacterial Potential of Gompang Batu Plant Extract (Lobelia nummularia Lam) Against Skin Disorder-Causing Bacteria - Syazwana Izni; Murniaty Simorangkir; Yesica Marcelina Romauli Sinaga (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
Skin disorders are common health problems that are often caused by bacterial infections such asStaphylococcus epidermis and Propionibacterium acnes. This study aims to analyze the antibacterialpotential of n-hexane, ethyl acetate, and ethanol extracts of gompang batu (Lobelia nummularia Lam)plants against bacteria that cause skin disorders. Extraction was carried out by maceration withsolvents of varying polarity. Antibacterial tests were carried out using the disc diffusion andmicrodilution methods with six treatments (chloramphenicol, DMSO, 1.25%; 2.5%; 5% and 10%extract). The results showed that the ethanol extract with a concentration of 10% had the most effectiveantibacterial activity with an inhibition zone of 14.0 mm (P. acnes bacteria) and 13.8 mm (S. epidermisbacteria). The MIC value of the extract ranged from 156.25 to 625 µg/mL and the MBC value of allextracts> 2500 µg/mL indicated bactericidal properties. Gompang batu has the potential as a naturalantibacterial for skin infections. N-hexane extract contains steroids and tannins; ethyl acetate containsalkaloids, flavonoids, steroids and tannins; ethanol contains alkaloids, flavonoids, terpenoids and tannins.